Cepharanthine hydrochloride: a novel ferroptosis-inducing agent for prostate cancer treatment - Guan, Jing-Song; Jia, Jing; Huang, Ze-Xiu; Zhou, Yu-Qing; Zheng, Jing-Jie; Lin, Qi-Man; Wang, Yi-Fei; Fan, Jiang-Lin; Wang, Yao (Frontiers in Pharmacology, 2025)
BackgroundFerroptosis is an intracellular iron-dependent cell death that is distinct from apoptosis, necrosis, and autophagy. Increasing evidence indicated that ferroptosis plays a crucial role in suppressing tumors, thus providing new opportunities for cancer therapy. The drug cepharanthine, commonly used to treat leukopenia, has been discovered to function as an anticancer agent to multiple types of cancer via diverse mechanisms. However, the effect of cepharanthine on prostate cancer remains unclear.MethodsA semi-synthetic derivative of cepharanthine, cepharanthine hydrochloride (CH), is used in this study due to its better water solubility and bioavailability. The prostate cancer cell lines LNCaP, 22Rv1, PC3 and xenograft mouse models are used for detecting the anti-tumor effect of CH in vitro and in vivo. Types of cell death including ferroptosis are detected by flow cytometry using annexin V and total/lipid reactive oxygen species probes, drug combination of CH with ferroptosis inhibitor/ion chelator, and the appearance of mitochondria under a transmission electron microscopy. The mechanism is investigated by high-throughput transcriptome analysis and transcription factor function analysis of androgen receptor.ResultsCH inhibits cellular functions and trigger ferroptosis in prostate cancer cells. Mechanistic research revealed both common and distinct pharmacological mechanisms of CH-induced ferroptosis in different prostate cancer cells. High-throughput transcriptome analysis revealed that ferroptosis-related genes are significantly regulated in androgen receptor-dependent cells 22Rv1 and LNCaP, and less significantly in androgen receptor-independent cell PC3. Furthermore, CH was found to reduce the gene expressions and protein levels of GPX4 and FSP1 through modulating the activity of the androgen receptor signaling pathway, but not through its transcription factor activity. In addition, CH upregulated ACSL4 and downregulated DHODH, with the combined regulatory outcomes synergistically inducing ferroptosis. An in vivo experiment employing CH and ion chelator-treated nude mice validated the mechanism by which CH induces ferroptosis to combat prostate cancer.ConclusionThis study has identified CH as a novel ferroptosis-inducing agent for the treatment of prostate cancer. The multiple mechanisms we found provides strong evidence for the eventual clinical application of the drug.